Arresting Ashley X: Trans Youth, Puberty Blockers and the Question of Whether Time is on Your Side. (March 2017) - Pyne, Jake
Abstract : In 2004, a young Seattle girl with significant disabilities known only by the pseudonym Ashley X, underwent a series of medical procedures without her consent. At the request of her parents, Ashley received a mastectomy, a hysterectomy and hormonal treatment, designed to arrest her development in a child-like state. In the eyes of her doctors, her family, and their lawyers, it was urgent that Ashley's body be aligned with her purported cognitive age. The temporal and ethical arguments used to justify her 'Treatment' turned Ashley's body into a site of international debate over disability and human rights, consent and medical science, eugenics and human engineering. Yet the similarities and differences between Ashley's non-consensual pubertal arrest versus that actively sought by trans youth are rarely mentioned. This paper uses the clinical and media discourses at work in both the 'Ashley Treatment' and the treatment sought by trans youth to think through this moment in which some bodies are treated to greater forms of autonomy while other bodies have none. I argue that the discourses used to secure transition for some trans youth ought to be weighed against the implications for others, in particular for trans youth with disabilities. While the availability of puberty suppression for trans youth can be narrated as a sign that things are getting better, the literatures of queer temporality and critical disability studies help to consider that it may also augur something else—a widening gap between those invested with the ability to stop time versus those who are stopped in time.